Broilers' toes asymmetry and walking ability assesment - Nääs, Irenilza de A.; Baracho, Marta Dos S.; Salgado, Douglas D.; Sonoda, Lilia T.; Carvalho, Victor R. C.; de Moura, Daniella J.; Paz, ibiara C. L. A. [UNESP] (FapUNIFESP (SciELO), 2009)
Economy due to its technological advancement, which associated to the development of genetic strains of high growth may cause deviation in the growth rate and harm production. Morphological asymmetry has been pointed as an indicator of welfare, as maintained the pattern that leads to balance, the broiler chicken would have its normal locomotion characteristics, freely reaching water and feed. Thus, the objective of this research was to verify the possibility of using morphological asymmetry for evaluating walking ability of broiler chicken. The research was done in the Technology Center, at UNICAMP. The experiment was made using biomechanics analysis and following, the toes were measured. Results found did not show asymmetry useful for determining the locomotion ability of broiler chicken. New studies are recommended in order to search for other correlations that might help to estimate at field level, the locomotion difficulties of broiler chicken.
Assimetria dos pés de frangos de corte e medida de habilidade locomotora
Keywords: Animal welfare; Biomechanics; Morphological asymmetry